Emerging nutritional supplements for strength and hypertrophy: an update of the current literature - Gonzalez, A. M.; Church, D. D.; Townsend, J. R.; Bagheri, R. (Strength and Conditioning Journal, 2020)
Several dietary supplements have been proposed as a means of improving muscle strength and hypertrophy when combined with resistance training. However, few have received sufficient attention from sports scientists to produce robust evidence for being well recommended. A growing body of literature has emerged for several dietary ingredients with the potential to promote muscular adaptations. Therefore, the aim of this review is to provide an evidence-based review of the efficacy of emerging nutritional supplements to allow athletes, coaches, and practitioners to make an informed decision when considering their use as a means of improving muscle strength and hypertrophy.